Imaging blood–brain barrier dysfunction in drug-resistant epilepsy: A multi-center feasibility study - Campbell, Matthew; Doherty, Colin (My University, 2024)
Objective: Blood–brain barrier dysfunction (BBBD) has been linked to various neurological disorders, including epilepsy. This study aims to utilize dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) to identify and compare brain regions with BBBD in patients with epilepsy (PWE) and healthy individuals. Methods: We scanned 50 drug-resistant epilepsy (DRE) patients and 58 control participants from four global specialized epilepsy centers using DCE-MRI. The presence and extent of BBBD were analyzed and compared between PWE and healthy controls. Results: Both greater brain volume and higher number of brain regions with BBBD were significantly present in PWE compared to healthy controls (p < 10−7). No differences in total brain volume with BBBD were observed in patients diag- nosed with either focal seizures or generalized epilepsy, despite variations in the affected regions. Overall brain volume with BBBD did not differ in PWE with MRI- visible lesions compared with non-lesional cases. BBBD was observed in brain regions suspected to be related to the onset of seizures in 82% of patients (n = 39) and was typically identified in, adjacent to, and/or in the same hemisphere as the suspected epileptogenic lesion (n = 10). Significance: These findings are consistent with pre-clinical studies that highlight the role of BBBD in the development of DRE and identify microvascular stabilization as a potential therapeutic strategy.
PUBLISHED
cited By 0
Keywords: biomarkers; blood–brain barrier; drug resistance; epilepsy; magnetic resonance imaging